Can youth-engaged research facilitate equitable access to contraception in Canada? The qualitative study protocol for the Ask Us project. Issue 3 (2nd March 2023) - Munro, Sarah; Di Meglio, Giuseppina; Williams, Aleyah; Barbic, Skye Pamela; Begun, Stephanie; Black, Amanda; Carson, Andrea; Fortin, Michelle; Jacob, Kaiya; Khan, Zeba; Martin-Misener, Ruth; Meherali, Salima; et al.
Abstract : Introduction: There is little to no evidence in Canada on the barriers that youth face when accessing contraception. We seek to identify the contraception access, experiences, beliefs, attitudes, knowledge, and needs of youth in Canada, from the perspectives of youth and youth service providers. Methods and analysis: This prospective, mixed-methods, integrated knowledge mobilisation study, the Ask Us project, will involve a national sample of youth, healthcare and social service providers, and policy makers recruited via a novel relational mapping and outreach approach led by youth. Phase I will centre the voices of youth and their service providers through in-depth one-on-one interviews. We will explore the factors influencing youth access to contraception, theoretically guided by Levesque's Access to Care framework. Phase II will focus on the cocreation and evaluation of knowledge translation products (youth stories) with youth, service providers, and policy makers. Ethics and dissemination: Ethical approval was received from the University of British Columbia's Research Ethics Board (H21-01091). Full open-access publication of the work will be sought in an international peer-reviewed journal. Findings will be disseminated to youth and service providers through social media, newsletters, and communities of practice, and to policy makers through invited evidence briefs and face-to-face presentations.